FDI-trade nexus: empirical analysis on ASEAN-5 - Kueh, Jerome Swee-Hui; Puah, Chin-Hong; Lau, Evan; Shazali, Abu Mansor (2007)
This paper investigates the dynamic linkages between FDI and trade of ASEAN-5 countries using the Autoregressive Distributed Lag (ARDL) bounds testing approach. Empirical results suggest that FDI and import are complement to each other in long run but import tends to substitute FDI in short run. Conversely, export tends to substitute FDI in long run, however, complementary linkage was found between FDI and export in short run.